2018
DOI: 10.1159/000493144
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Remifentanil-Induced Hyperalgesia by Betulinic Acid Associates with Inhibiting Oxidative Stress and Inflammation in Spinal Dorsal Horn

Abstract: Remifentanil-induced hyperalgesia (RIH) is known to be associated with oxidative stress and inflammation. Betulinic acid (BA) was reported to reduce visceral pain owing to its anti-oxidative and anti-inflammatory potential. Here, we ­explored whether BA can attenuate RIH through inhibiting oxidative stress and inflammation in spinal dorsal horn. Sprague-Dawley rats were randomly divided into 4 groups: Control, Incision, RIH, and RIH pre-treated with BA. After pretreated with BA (25 mg/kg, i.g.) for 7 days, rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Heme oxygenase 1 and eNOS also have antioxidant activity (Sun et al, 2018). Pretreatment with BA decreases oxidative stress, effectively alleviating remifentanil-induced hyperalgesia (Lv et al, 2018). The IHC and Western blotting results demonstrated that SOD1, eNOS, and HO1 expression in the dermis of skin flaps was enhanced in the BA group.…”
Section: Discussionmentioning
confidence: 99%
“…Heme oxygenase 1 and eNOS also have antioxidant activity (Sun et al, 2018). Pretreatment with BA decreases oxidative stress, effectively alleviating remifentanil-induced hyperalgesia (Lv et al, 2018). The IHC and Western blotting results demonstrated that SOD1, eNOS, and HO1 expression in the dermis of skin flaps was enhanced in the BA group.…”
Section: Discussionmentioning
confidence: 99%
“…Hong et al 35 reported that spinal astrocyte activation and inflammatory reaction are involved in RIH. Lv et al 36 reported that the attenuation of RIH by betulinic acid was associated with a potential inhibition of oxidative stress and subsequent downregulation of IL-1β in the spinal dorsal horn. The current study showed that intraoperative infusion of remifentanil downregulated the nociceptive thresholds (PWT and PWL) at different time points (2, 6, 24, and 48 h) during the postoperative period ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis including 27 studies reported signi cant increases in acute pain after general anesthesia with remifentanil, leading to higher morphine requirements [16]. The roles of ROS and in ammation in OIH have attracted much attention [17]. It has been reported that remifentanil stimulates overproduction of proin ammatory cytokines and ROS, leading to the activation of neuronal NMDA receptors, which play an important role in OIH [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that remifentanil stimulates overproduction of proin ammatory cytokines and ROS, leading to the activation of neuronal NMDA receptors, which play an important role in OIH [18,19]. Also, excessive MMP-9 activity induced by remifentanil mediates extracellular matrix abnormalities, which can lead to a variety of neuropathological conditions including neuroin ammation and hyperalgesia [17,[20][21][22]. However, these effects have only been reported in animal studies.…”
Section: Discussionmentioning
confidence: 99%